A Computational Investigation of Myelination and Epilepsy - Dumas, Odin (Université d'Ottawa | University of Ottawa, 2024)
Epilepsy, characterized by recurrent seizures, is one of the most prevalent neurological dis- eases worldwide. Recent advances suggest that myelination, the insulating sheaths around axons of neurons, plays a crucial role in the neuronal network’s functionality and might influence epilepsy. This thesis explores the relationship between myelination and the dynamics of epilepsy through computational modeling, specifically with the Wilson-Cowan model, a well-established framework for understanding interactions within neural popula- tions. We modified the traditional Wilson-Cowan equations to incorporate variables repre- senting myelination and conducted simulations to observe how changes in myelination affect seizure activity in neural networks. The results indicate that increases in myelination along specific tracts can significantly alter the excitatory and inhibitory dynamics of neural popu- lations, leading to increased seizure burden. These findings could provide new insights into epilepsy management and suggest myelination as a target for novel therapeutics. This study not only enhances our understanding of epilepsy’s pathophysiology but also underscores the importance of myelination in neural circuits and disease progression. L’épilepsie, caractérisée par des crises récurrentes, est l’une des maladies neurologiques les plus prévalentes dans le monde. Des avancées récentes suggèrent que la myélinisation, les gaines isolantes autour des axones des neurones, joue un rôle crucial dans la fonctionnalité du réseau neuronal et pourrait influencer l’épilepsie. Cette thèse explore la relation entre la myélinisation et la dynamique de l’épilepsie à travers la mod élisation computationnelle, spécifiquement avec le modèle de Wilson-Cowan, un cadre bien établi pour comprendre les interactions au sein des populations neuronales. Nous avons modifié les équations tradition- nelles de Wilson-Cowan pour incorporer des variables représentant la myélinisation et avons mené des simulations pour observer comment les changements dans la myélinisation affectent l’activité des crises dans les réseaux neuronaux. Les résultats indiquent que les augmentations de la myélinisation le long de tracts spécifiques peuvent modifier significativement les dynamiques excitatrices et inhibitrices des populations neuronales, conduisant à une augmentation du fardeau des crises. Ces découvertes pourraient offrir de nouvelles perspectives dans la gestion de l’épilepsie et suggèrent la myélinisation comme cible pour de nouveaux traitements thérapeutiques. Cette étude améliore non seulement notre compréhension de la physiopathologie de l’épilepsie, mais souligne également l’importance de la myélinisation dans les circuits neuronaux et la progression de la maladie.
Keywords: Myelination; Epilepsy; Computational; Neuroscience; Heterogeneity